Isolated Rib Fractures in Elderly Falls: Not As Deadly As We Think. Issue 2 (March 2022) - Cull, John D.; Ewing, Alex; Metcalf, Ashley; Kitchens, Debra; Manning, Benjamin
Abstract : BACKGROUND: Rib fractures in elderly patients have been associated with high morbidity and mortality; however, many of these patients had substantial mechanisms of injury, which may have contributed to these high rates. OBJECTIVE: The purpose of this study was to determine the morbidity and mortality of elderly patients with isolated rib fractures who fell from standing. METHODS: A single-institution retrospective study was conducted in a Level I trauma center using the trauma registry and a separate elderly fall from standing database. Admitted patients 65 years or older who presented with rib fractures after a fall from January 2013 to June 2017 were included. Patients with a nonthoracic Abbreviated Injury Scale score greater than 2 were excluded from the study. RESULTS: Of 129 patients with isolated rib fracture, 94% ( n = 121) had comorbidities and 71% ( n = 92) had two or more comorbidities. Almost half (41.9%; n = 54) were taking antiplatelet and anticoagulant medications, 78.3% ( n = 101) were caused by a mechanical fall, and 7% ( n = 9) were caused by syncope. Data showed 72.9% ( n = 94) had three or more rib fractures. The mortality rate of patients was 3.9% ( n = 5). Three patients had dementia at death, four had do-not-resuscitate order, and only two deaths were directly related to pulmonary status. Patients who developed pneumonia (14.7%; n = 19) and required mechanical ventilation for a median of 11 days (3.9%; n = 5) were fewer than those in in previous studies. CONCLUSION: The morbidity and mortality associated with rib fractures are significantly less than reported in the literature when additional injuries are excluded.